Kualitas Fisik dan Organoleptik Bakso Ayam dengan Penambahan Tepung Talas (Colocasia Esculenta (L) Schoot) pada Konsentrasi yang Berbeda - Masyitah Masyitah; Siti Asyura (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
This study aims to determine the pH quality and organoleptic quality (color, aroma, taste and texture) of broiler chicken meatballs with the addition of talas flour. This study used three treatment (10%,20%,30%) each repeated six time so that obtained. The designs used were Completely Randomized Design (CRD). The results showed that the addition of talas flour had a significant effect (P<0,01) on the colour, taste, texture and had no effect on the pH and aroma in meatball product.